2014
DOI: 10.1007/s00604-014-1420-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual and microplate detection of aflatoxin B2 based on NaCl-induced aggregation of aptamer-modified gold nanoparticles

Abstract: We describe a fast and sensitive method for the detection of aflatoxin B2 (AFB2) that is based on the addition of AFB2-sensitive aptamers to a colloidal solution of gold nanoparticles (AuNPs). Subsequent addition of AFB2 and NaCl to the solution causes a color change from wine-red to blue-purple. Best results are obtained at a pH value of 7.0, a 10 mM aptamer concentration, and a 2 M concentration of NaCl. The method has a linear dynamic range that extends from 0.025 to 10 ng mL −1 of AFB2, and the detection l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In order to optimize the NaCl concentration, AuNPs were treated with different volumes of 2 M NaCl solution (0, 10,15,20,25,30,35, and 40 μL) and MOPS buffer were added to attain a total volume of 500 μL. After incubating for 5 min, A520 and A650 were recorded, and the minimum NaCl concentration that can fully induce aggregation of AuNPs was chosen.…”
Section: Optimization Of Detection Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to optimize the NaCl concentration, AuNPs were treated with different volumes of 2 M NaCl solution (0, 10,15,20,25,30,35, and 40 μL) and MOPS buffer were added to attain a total volume of 500 μL. After incubating for 5 min, A520 and A650 were recorded, and the minimum NaCl concentration that can fully induce aggregation of AuNPs was chosen.…”
Section: Optimization Of Detection Conditionsmentioning
confidence: 99%
“…Thus, several metal ions and small organic molecules have been detected through the unmodified AuNP-based colorimetric assays [22]. Additionally, NaCl have been employed to control the aggregation of AuNPs, which received excellent results [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…After that, the target-induced conformational change exposes the AuNPs to NaCl-induced aggregation leading to a colour change. The linear dynamic range and detection sensitivity were found to be 0.025–100 µg/L and 0.025 µg/L of AFB1, respectively [77,78]. Seok et al reported another colorimetric assay based on AFB1-induced DNA structural changes and peroxidase mimicking DNAzyme.…”
Section: Label-free Aptasensors For Myctotoxin Determinationmentioning
confidence: 99%
“…2), the present study reports the synthesis of desert rose-like GNPs (DR-GNPs), their characterization by means of UV-vis absorption spectroscopy, transmission electron microscopy (TEM) and dynamic light scattering (DLS) and their use as labels for ICST. Although other ligands have been reported, such as for example aptamers [14][15], the large majority of GNP-based ICSTs reported in the literature and commercially available use antibodies as recognition elements [16][17] and most frequently the labeling of antibodies with GNPs is achieved through passive adsorption of proteins on their surfaces. Therefore, a preliminary study on the passive adsorption of antibodies on DR-GNPs as a function of the pH and the amount of antibody (Ab) used for conjugation with DR-GNP was conducted.…”
Section: Introductionmentioning
confidence: 99%